2015
DOI: 10.1016/j.actamat.2015.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of interfacial curvatures of a bicontinuous structure generated via nonconserved dynamics

Abstract: While coarsening of spherical particles has been well documented, our understanding of coarsening of complex microstructures is still limited. The first step in developing a theory of coarsening of microstructures with complex morphologies is to study coarsening of microstructures that evolve self-similarly. In this paper, we examine the morphological evolution of a self-similar two-phase bicontinuous structure generated via nonconserved dynamics (i.e., motion by mean curvature) to elucidate the complex dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…In our previous effort, we examined the morphological evolution of a bicontinuous structure undergoing coarsening via nonconserved dynamics [32]. We observed that, while the majority of interfaces undergo flattening, some regions of interfaces become more highly curved as they approach pinching (a topological singularity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous effort, we examined the morphological evolution of a bicontinuous structure undergoing coarsening via nonconserved dynamics [32]. We observed that, while the majority of interfaces undergo flattening, some regions of interfaces become more highly curved as they approach pinching (a topological singularity).…”
Section: Introductionmentioning
confidence: 99%
“…of static interfacial properties, namely the local curvatures, H and K , and the nonlocal interfacial property, D S H [32]. In conserved dynamics, even though v is not proportional to the mean curvature, the statistical analysis in Sec.…”
mentioning
confidence: 99%
“…In recent years, numerical modeling has become an important research method to study microstructural evolution during various phase transformation processes. Phase-field (PF) models have been applied to simulate dendrite arm coarsening [31][32][33] and fragmentation [34]. Cool and Voorhees [33] took a three-dimensional dendritic structure of Pb-Sn alloy measured from experiments as an initial condition in a phase-field simulation to investigate the coarsening dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Phase-field (PF) simulations have been performed to investigate dendrite coarsening 24 28 and dendrite fragmentation 29 . In those simulations, the evolution of dendrite morphology during holding in mushy zones was appropriately reproduced.…”
Section: Introductionmentioning
confidence: 99%